2013
DOI: 10.1021/jp4013224
|View full text |Cite
|
Sign up to set email alerts
|

A Quantum Alloy: The Ligand-Protected Au25–xAgx(SR)18 Cluster

Abstract: Recent synthetic advances have produced very small (sub-2 nm), ligand-protected mixed-metal clusters. Realization of such clusters allows the investigation of fundamental questions: (1) Will heteroatoms occupy specific sites within the cluster? (2) How will the inclusion of heteroatoms affect the electronic structure and chemical properties of the cluster? (3) How will these very small mixed-metal systems differ from larger, more traditional alloy materials? In this report we provide experimental and computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
99
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 72 publications
12
99
0
Order By: Relevance
“…Because the Au/Ag NCs possess a lower 4f 7/2 binding energy than that of bare Au NCs, we believe that this is caused by the Au-Ag charge redistribution that occurred within the clusters, which balances the electron-withdrawing effects of the thiolate ligand. This phenomenon has been previously observed for Au 25-x Ag x clusters [22,47].…”
Section: Figuresupporting
confidence: 82%
“…Because the Au/Ag NCs possess a lower 4f 7/2 binding energy than that of bare Au NCs, we believe that this is caused by the Au-Ag charge redistribution that occurred within the clusters, which balances the electron-withdrawing effects of the thiolate ligand. This phenomenon has been previously observed for Au 25-x Ag x clusters [22,47].…”
Section: Figuresupporting
confidence: 82%
“…In addition, the Pd 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 3d 3/2 XPS peak observed at 341.4 eV, which corresponds to Pd 0 , suggests that Pd atom is located at the center of PdAu 24 (SR) 18 ; a positive shift would be expected if it was located at the surface of the core or in the ligand shell. 19,32,38 Similarly, the Pt 4f 5/2 and 4f 7/2 peaks observed at respectively 75.1 and 71.8 eV suggest that the doped Pt atom is located at the center of PtAu 24 (SR) 18 . 32 Transmission electron microscopy (TEM) images of the isolated PdAu 24 (SR) 18 and PtAu 24 (SR) 18 clusters in SI Figure S2 show that the average core sizes are both around 1.…”
Section: Resultsmentioning
confidence: 97%
“…108 18 and reported that, because Ag doping 35 raises the orbital energy of the cluster's LUMO, the HOMO−LUMO gap is increased. 111 All these results indicate that Ag doping is an effective means of creating stable clusters with larger HOMO−LUMO gaps than the original magic Au 25 (SR) 18 . 24 and Au 144-n Ag n (SR) 60 40 Regarding the larger Ag-doped clusters, Dass et al have successfully synthesized larger Ag-doped magic Au n (SR) m clusters, with up to 12 Ag atoms in Au 38 (SC 2 H 4 Ph) 24 and up to 60 in Au 144 (SC 2 H 4 Ph) 60 .…”
Section: Electronic Structuresmentioning
confidence: 96%